2013
DOI: 10.1073/pnas.1214312110
|View full text |Cite
|
Sign up to set email alerts
|

Intraislet SLIT–ROBO signaling is required for beta-cell survival and potentiates insulin secretion

Abstract: We previously cataloged putative autocrine/paracrine signaling loops in pancreatic islets, including factors best known for their roles in axon guidance. Emerging evidence points to nonneuronal roles for these factors, including the Slit-Roundabout receptor (Robo) family, in cell growth, migration, and survival. We found SLIT1 and SLIT3 in both beta cells and alpha cells, whereas SLIT2 was predominantly expressed in beta cells. ROBO1 and ROBO2 receptors were detected in beta and alpha cells. Remarkably, even m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 56 publications
4
58
0
Order By: Relevance
“…Besides functioning as axon guidance molecules, the Slit/Robo pathway proteins also regulate functions such as morphogenesis of tissue as well as performing many non-neuronal roles such as cell growth, migration and cell survival [92]. Slit/Robo is often downregulated in the advanced stage of most tumors [31,85,86].…”
Section: Future Prospects For Slit/robo Pathway As a Drug Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides functioning as axon guidance molecules, the Slit/Robo pathway proteins also regulate functions such as morphogenesis of tissue as well as performing many non-neuronal roles such as cell growth, migration and cell survival [92]. Slit/Robo is often downregulated in the advanced stage of most tumors [31,85,86].…”
Section: Future Prospects For Slit/robo Pathway As a Drug Targetmentioning
confidence: 99%
“…Slit/Robo is often downregulated in the advanced stage of most tumors [31,85,86]. In vitro studies suggested that expression of Slit can be regulated by stress and optimum function can be achieved by modulating the endoplasmic reticulum (ER), Ca 2+ homeostasis and actin in β cells [92]. For example, cytokines, thapsigargin and palmitate suppress Slit2 expression and serum deprivation downregulates Slit3 [92].…”
Section: Future Prospects For Slit/robo Pathway As a Drug Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…While depth and coverage remain technical hurdles, these approaches will soon shed much-needed light on the functional heterogeneity of human islet cell subtypes and states, as well as the variability observed in in vitro derived cultures. Although insulin is by far the major secreted product of primary beta cells, this cell type likely expresses hundreds of other secreted proteins [52], several of which have known physiological roles [52][53][54]. Future studies should also address the completeness of insulin processing, as it is possible that improperly processed and/or secreted insulin can provoke or accelerate beta cell directed autoimmunity [55].…”
Section: Remaining Obstacles-deep Phenotypingmentioning
confidence: 99%
“…Measurements of intracellular calcium concentration for individual human islets from the different treatment groups were carried out by previously described methods (25,26) at glucose concentrations of 2.5 and 25 mmol/L. Glucose-stimulated increase in intracellular calcium concentration was expressed as area under the curve (AUC).…”
Section: Calcium Imagingmentioning
confidence: 99%